The relationship of energy intake, menstruation duration, and anemia symptoms in adolescent girls - Dina Larinci Utami; Dini Junita; Aripin Ahmad (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
An adolescent girl is categorized into a group prone to anemia. The prevalence of anemia in Indonesia is quite high because the iron nutritional anemia rate in Indonesia is 72.3%. Iron deficiency in adolescents causes paleness, weakness, fatigue, dizziness, and decreased concentration when learning. This study employed a quantitative method with a cross-sectional approach to determine the relationship of energy intake, menstruation duration, and anemia symptoms of adolescent girls at Senior High School 6 Jambi. This study was conducted in December 2020. The research population was 434 adolescent girls in grades 11 and 12 at Senior High School 6 Jambi City. Meanwhile, 70 samples were selected using a random sampling technique. The data were analyzed univariately and bivariately using the chi-square test. The results of the univariate analysis showed that 24.3% of the respondents experienced symptoms of anemia, 74.3% had a lack of energy intake, and 42.9% had long menstrual periods. The bivariate analysis discovered that there was a relationship between energy intake and anemia symptoms of adolescent girls with a p-value = 0.031. Moreover, there was a relationship between the menstruation period and anemia symptoms of adolescent girls with a p-value = 0.018. The school is suggested to improve their students’ health by revitalizing the school health unit and the youth red cross and screening students with health problems, especially anemia in young girls.